Higher skin carotenoid levels are associated with lower risks of metabolic syndrome: a cross-sectional study in Vietnamese participants - Yoshida, Kazutaka; Nakazawa, Yuichiro; Nguyen, Thuy Lan; Nguyen, Duc Huy; Anh, Chu Xuan; Takahashi, Shingo; Suzuki, Shigenori; Binh, Vu Quoc (Frontiers in Nutrition, 2026)
IntroductionMetabolic syndrome (MetS) is a major health concern in Vietnam. Although carotenoids have been suggested to suppress MetS, there has been no research on the relationship between carotenoid levels in the body and MetS risk in Vietnam. Therefore, this study clarified the relationship between skin carotenoid levels and markers related to MetS in Vietnamese adults using Vegecheck®, a device for non-invasively measuring skin carotenoid levels.MethodsThis cross-sectional study included 300 participants, and data were collected at the Dr. Binh TeleClinic, a hospital in Hanoi, Vietnam. Data on skin carotenoid levels, anthropometric parameters (height, weight, and body fat percentage), blood pressure, and blood parameters (glucose, triglyceride, and high- and low-density lipoprotein cholesterol levels) were collected. MetS risk counts were defined as the number of MetS components in accordance with international standards for MetS. Additionally, participants answered questions regarding their attributes and lifestyles using a simple questionnaire.ResultsAfter excluding 22 participants with missing data, 278 participants were included in the analysis. The average skin carotenoid levels in all participants were 5.41 ± 1.31, 4.99 ± 1.10 in men, and 5.67 ± 1.37 in women. Higher skin carotenoid levels were associated with lower MetS risk counts. The odds ratio (OR), with 95% confidence interval (CI), was 0.767 [0.645–0.910] (p = 0.003). Skin carotenoid levels are significantly negatively associated with body weight, body mass index, blood glucose, and triglyceride levels. The estimated regression coefficient and 95% CI after multivariable adjustment were −0.016 [−0.0301, −0.0011] (p = 0.034), −0.018 [−0.0305, −0.0045] (p = 0.008), −0.043 [−0.0686, −0.0177] (p < 0.001), and −0.090 [−0.1429, −0.0374] (p < 0.001), respectively.ConclusionThis study indicates a relationship between carotenoid levels and MetS risk in Vietnamese individuals, although a causal relationship between carotenoid intake and MetS could not be established. This study has some limitations, such as the influence of unknown confounding factors and selection bias, and the unclearness of individual carotenoids’ effects. Future observational and intervention studies taking these limitations into account are required.Clinical trial registrationClinicalTrials.gov, identifier NCT06271070.